Individual effects and dynamics in count data models - Richard Blundell; Rachel Griffith; Frank Windmeijer (Institute for Fiscal Studies (IFS), 1999)
In this paper we examine the panel data estimation of dynamic models for count data that include correlated fixed effects and predetermined variables.
Keywords: C23; C25; O30; 330; dtnamic count panel data; individual effects; predetermined regressors; Generalised Method of Moments; pre-smaple information